2021
DOI: 10.33594/000000437
|View full text |Cite
|
Sign up to set email alerts
|

P. aeruginosa Induced Lipid Peroxidation Causes Ferroptotic Cell Death in Airways

Abstract: BACKGROUND/AIMS: Oxidative stress and infections by Pseudomonas aeruginosa (P. aeruginosa) are prominent in lungs of patients suffering from cystic fibrosis (CF). METHODS: The present study examines effects of P. aeruginosa on lipid peroxidation in human and mouse lungs, and cell death induced by P. aeruginosa in human airway epithelial cells. The role of the Ca2+ activated Cl- channel TMEM16A, the phospholipid scramblase TMEM16F, and the CFTR Cl- channel for ferroptotic cell death is examined. RESULTS: Lipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…Although this enzyme is involved in cell lipid oxidation, it is unlikely the root cause of increased lipid peroxidation and subsequent ferroptosis observed in the macrophages here. Lipid peroxidation is a hallmark of CF 70,71 and ferroptosis was recently described in CF epithelial cells [72][73][74] . Our study expands the current understanding of how P. aeruginosa can induce ferroptosis in CF, showing that 1) multidrug-resistant P. aeruginosa can induce ferroptosis in macrophages, one of the most important cell types in bacterial clearance [4][5][6][7] , and 2) RNase E variants can confer bacterial hypervirulence by triggering host cell ferroptosis.…”
Section: Discussionmentioning
confidence: 98%
“…Although this enzyme is involved in cell lipid oxidation, it is unlikely the root cause of increased lipid peroxidation and subsequent ferroptosis observed in the macrophages here. Lipid peroxidation is a hallmark of CF 70,71 and ferroptosis was recently described in CF epithelial cells [72][73][74] . Our study expands the current understanding of how P. aeruginosa can induce ferroptosis in CF, showing that 1) multidrug-resistant P. aeruginosa can induce ferroptosis in macrophages, one of the most important cell types in bacterial clearance [4][5][6][7] , and 2) RNase E variants can confer bacterial hypervirulence by triggering host cell ferroptosis.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to manipulation of host lipid mediator–driven responses, recent studies have identified exploitation of host lipid peroxidation pathways as a virulence strategy of PAO1 ( 12 , 43 , 44 ). The process of ferroptosis is driven by peroxidation of PUFA-phospholipids and accumulation of unstable hydroperoxy-phospholipids — which can be cleaved to toxic levels of oxidatively truncated electrophilic products attacking nucleophilic sites in target proteins — if the regulatory reduced glutathione (GSH)/GPx4 system fails to reduce them to the more stable alcohols ( 11 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…aeruginosa has been supported by 2 recent independent studies, by Bagayoko et al and Ousingsawat et al, which also highlighted and documented the critical role of P . aeruginosa induced ferroptosis in the pathology of pneumonia and cystic fibrosis ( 43 , 44 ). Here, by using a lipoxygenase inhibitor, baicalein, we demonstrate that this increased lethality of PAO1 infection after irradiation is due, at least in part, to pLoxA-stimulated ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that neutrophil infiltration and lung cell apoptosis or necroptosis may not be important contributors to CS primed P. aeruginosa -triggered ALI. P. aeruginosa has recently been shown to induce lipid peroxidation, leading to ferroptotic cell death in human airway epithelial cells [ [43] , [44] , [45] ]. Future studies are needed to address if lipid peroxidation and ferroptotic cell death contributes to CS priming PA-triggered ALI.…”
Section: Discussionmentioning
confidence: 99%